2022
DOI: 10.1097/anc.0000000000001028
|View full text |Cite
|
Sign up to set email alerts
|

Using the Eat Sleep Console Model to Promote Optimal Care and Outcomes for Infants With Neonatal Abstinence Syndrome

Abstract: Background: A nurse led a team of providers in a quality improvement (QI) project to positively impact inpatient care and outcomes for infants with neonatal abstinence syndrome (NAS). The Eat Sleep Console (ESC) model was implemented to promote rooming-in and family-centered care as part of a nonpharmacological treatment approach. Purpose: To compare the ESC model with the traditional Finnegan treatment approach to describe differences in infants' pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In response to these challenges, we adopted a familycentered, nonpharmacological approach called "Eat, Sleep, Console (ESC)." [8][9][10][11] This approach prioritizes feeding, sleeping, and consoling the infants as primary management strategies for NOWS. 8 A study conducted by Grossman et al in 2017 demonstrated a significant decrease in length of stay (LOS) from 22.4 to 5.9 days and a substantial reduction in morphine use from 98% to 14% after implementing a quality improvement (QI) approach that centered around nonpharmacological therapies and a simplified assessment using the ESC model.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these challenges, we adopted a familycentered, nonpharmacological approach called "Eat, Sleep, Console (ESC)." [8][9][10][11] This approach prioritizes feeding, sleeping, and consoling the infants as primary management strategies for NOWS. 8 A study conducted by Grossman et al in 2017 demonstrated a significant decrease in length of stay (LOS) from 22.4 to 5.9 days and a substantial reduction in morphine use from 98% to 14% after implementing a quality improvement (QI) approach that centered around nonpharmacological therapies and a simplified assessment using the ESC model.…”
Section: Introductionmentioning
confidence: 99%